LYS3 encodes a prolamin-box-binding transcription factor that controls embryo growth in barley and wheat. (May 2020) - Orman-Ligeza, Beata; Borrill, Philippa; Chia, Tansy; Chirico, Marcella; Doležel, Jaroslav; Drea, Sinead; Karafiátová, Miroslava; Schatlowski, Nicole; Solomon, Charles U.; Steuernagel, Burkhard; Wulff, Brande B.H.; Uauy, Cristobal; et al.
Abstract: Mutations at the LYS3 locus in barley have multiple effects on grain development, including an increase in embryo size and a decrease in endosperm starch content. The gene underlying LYS3 was identified by genetic mapping and mutations in this gene were identified in all four barley lys3 alleles. LYS3 encodes a transcription factor called Prolamin Binding Factor (PBF). Its role in controlling embryo size was confirmed using wheat TILLING mutants. To understand how PBF controls embryo development, we studied its spatial and temporal patterns of expression in developing grains. The PBF gene is expressed in both the endosperm and the embryos, but the timing of expression in these organs differs. PBF expression in wild-type embryos precedes the onset of embryo enlargement in lys3 mutants, suggesting that PBF suppresses embryo growth. We predicted the down-stream target genes of PBF in wheat and found them to be involved in a wide range of biological processes, including organ development and starch metabolism . Our work suggests that PBF may influence embryo size and endosperm starch synthesis via separate gene control networks. Graphical abstract: Image 1 Highlights: LYS3 encodes a transcription factor called Prolamin Binding Factor (PBF) that is expressed in grains only. Wheat and barley LYS3 / PBF mutants have enlarged embryos suggesting that this gene suppresses embryo growth. The predicted targets of wheat PBF are involved in a wide range of biological processes, including organ development.